2017
DOI: 10.1038/srep44449
|View full text |Cite
|
Sign up to set email alerts
|

The development of novel LTA4H modulators to selectively target LTB4 generation

Abstract: The pro-inflammatory mediator leukotriene B4 (LTB4) is implicated in the pathologies of an array of diseases and thus represents an attractive therapeutic target. The enzyme leukotriene A4 hydrolase (LTA4H) catalyses the distal step in LTB4 synthesis and hence inhibitors of this enzyme have been actively pursued. Despite potent LTA4H inhibitors entering clinical trials all have failed to show efficacy. We recently identified a secondary anti-inflammatory role for LTA4H in degrading the neutrophil chemoattracta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…However, similar to what was reported recently by Low et al . 15 , these compounds turned out to inhibit both activities of the enzyme and were not epoxide hydrolase selective. Indeed, we found that close and even smaller analogues of ARM1 and 4-MDM also failed to show any selectivity for the epoxide hydrolase function of the enzyme (Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, similar to what was reported recently by Low et al . 15 , these compounds turned out to inhibit both activities of the enzyme and were not epoxide hydrolase selective. Indeed, we found that close and even smaller analogues of ARM1 and 4-MDM also failed to show any selectivity for the epoxide hydrolase function of the enzyme (Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…Recent reports, however, have described small fragments that utilize almost exclusively the hydrophobic LTA4 binding site. These fragments were claimed not to interfere with PGP degradation or to even augment the peptidase activity of the enzyme 12 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, this resulted in a modest reduction in CF exacerbations in a recent phase IIb trial. It could be argued that Acebilustat would inadvertently lead to PGP accumulation, which in turn could mask some of the benefits of ameliorating LTB 4 -driven inflammation [ 41 ]. However, our current study demonstrates that PGP degradation by LTA 4 H is already aberrant in CC-CF children, potentially owing to degradation of LTA 4 H by neutrophil elastase, and thus it is feasible that any potential adverse effects of Acebilustat in inhibiting PGP degradation by LTA 4 H would be negligible in CF.…”
Section: Discussionmentioning
confidence: 99%
“…Third, experiments aimed at determining the roles of the aminopeptidase activity of LTA 4 H in obesity would be of great interest. LTA 4 H inhibitors are currently being developed, [35][36][37] and LTA 4 H inhibition might increase HFDinduced thermogenesis, which would make it a promising therapeutic target for obesity.…”
Section: Discussionmentioning
confidence: 99%